Methodology for the improvement of the tactical technical action of baseball pitchers - Victor Oreste Cordero Valdés; Pedro Alberto Martínez Hernández; Rosa María Tabares Arévalo (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2019)
The technical tactical action of baseball pitchers requires the search for new tools that are derived in a pedagogical context that creatively manages the forms of knowledge, in line with this, the methodologies used in baseball demand a continuous updating in the theoretical, methodological and practical order. Hence, the objective of the present research was to develop a methodology for improving the tactical technical action of baseball pitchers in correspondence with the function they perform within the game. In order to do this, we worked with a primary sample of 15 pitchers from the Pinar del Río team, in the last year of the 17-18 category, as well as a secondary sample of 12 coaches, 20 specialists and 20 athletes who regularly or occasionally enter as pitchers. Scientific research methods and techniques such as document analysis, observation, standardized and individual interviews and expert judgment were used. There were shortcomings in the treatment of the contents of the tactical technical preparation for improving the actions of the baseball pitcher according to the role played in the game, from which a methodology is proposed that contains the structure, content and planning of the technical-tactical preparation of baseball pitchers, according to their function in the game, from simplified situations that didactically act on the components of this sports preparation and under laws and principles of sports training.